2019
DOI: 10.1111/bjd.17632
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and management of actinic keratosis in primary and secondary care: a complementary database analysis

Abstract: Summary Background The high prevalence of actinic keratosis (AK) requires the optimal use of healthcare resources. Objectives To gain insight in to the healthcare utilization of people with AK in a population‐based cohort, and the management of AK in a primary and secondary care setting. Methods A retrospective cohort study using three complementary data sources was conducted to describe the use of care, diagnosis, treatment and follow‐up of patients with AK in the Netherlands. Data sources consisted of a popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 40 publications
2
38
0
1
Order By: Relevance
“…This qualitative study confirms the previously found quantitative variation in AK management within and between primary and secondary care 12 and reveals the underlying motives reported by GPs and dermatologists. In contrast to dermatologists, GPs reported limitedly conducting proactive clinical assessment of cutaneous photodamage, mainly due to a perceived lack of value.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This qualitative study confirms the previously found quantitative variation in AK management within and between primary and secondary care 12 and reveals the underlying motives reported by GPs and dermatologists. In contrast to dermatologists, GPs reported limitedly conducting proactive clinical assessment of cutaneous photodamage, mainly due to a perceived lack of value.…”
Section: Discussionsupporting
confidence: 89%
“…either in a face-to-face setting (n = 28) or by telephone (n = 12). A predefined topic guide based on prior experiences of the authors 12,19,20 was used for the interviews and included the following main themes: AK care in general, diagnosis of AK, treatment of AK and follow-up care of AK (Appendix S1; see Supporting Information). Participants were asked to complete a short questionnaire to provide demographic information.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of the BJD , Noels and colleagues report on their study of healthcare utilization for AKs in the Netherlands . They highlight large differences in practice among primary care services and dermatologists.…”
mentioning
confidence: 99%